2014
DOI: 10.1089/fpd.2013.1682
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Kinetics of Various Chemical Disinfectants on Aeromonas hydrophila Planktonic Cells and Biofilms

Abstract: The present article focuses on the inactivation kinetics of various disinfectants including ethanol, sodium hypochlorite, hydrogen peroxide, peracetic acid, and benzalkonium chloride against Aeromonas hydrophila biofilms and planktonic cells. Efficacy was determined by viable plate count and compared using a modified Weibull model. The removal of the biofilms matrix was determined by the crystal violet assay and was confirmed by field-emission scanning electron microscope. The results revealed that all the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Aeromonads within a biofilm are more resistant to disinfectants than planktonic cells, as shown for A. hydrophila strains (Jahid and Ha, 2014). Aeromonads have thus been recovered from biofilm in drinking-water distribution systems (Chauret et al, 2001; September et al, 2007), even when water supply is chlorinated (Fernández et al, 2000).…”
Section: Biofilm Formation In Aeromonasmentioning
confidence: 84%
“…Aeromonads within a biofilm are more resistant to disinfectants than planktonic cells, as shown for A. hydrophila strains (Jahid and Ha, 2014). Aeromonads have thus been recovered from biofilm in drinking-water distribution systems (Chauret et al, 2001; September et al, 2007), even when water supply is chlorinated (Fernández et al, 2000).…”
Section: Biofilm Formation In Aeromonasmentioning
confidence: 84%
“…In fact, the disinfection by SH is greatly dependent on the strains of bacteria. Jahid and Ha () reported reductions of 6.5 and 6.7 log CFU/cm 2 after a 30‐min treatment with SH of Aeromonas hydrophila planktonic cells, whereas similar effects have been observed with 2000 and 4000 mg/L for biofilm cells, and in a recent study, SH was not very effective in killing biofilms (Pagedar & Singh, ). The presence of organic materials can also decrease the bactericidal effect of disinfectants along with a decrease in the ACC (Fukuzaki, ).…”
Section: Discussionmentioning
confidence: 66%
“…Sodium hypochlorite solutions have been widely used for hard‐surface disinfection, even in our homes, with known efficiency, while amphoteric surfactants, although efficient in many cases, are also know to induce resistance (McDonnell & Russel, ). Jahid & Ha () demonstrated that sodium hypochlorite was more efficient in removing aeromonads biofilm from polystyrene, as well as changing cell morphology, when compared with chemical disinfectants such as ethanol, hydrogen peroxide and benzalkonium chloride. Furthermore, Wirtanen et al .…”
Section: Resultsmentioning
confidence: 99%
“…Sodium hypochlorite solutions have been widely used for hard-surface disinfection, even in our homes, with known efficiency, while amphoteric surfactants, although efficient in many cases, are also know to induce resistance (McDonnell & Russel, 1999). Jahid & Ha (2014) demonstrated that sodium hypochlorite was more efficient in removing aeromonads biofilm from polystyrene, as well as changing cell morphology, when compared with chemical disinfectants such as ethanol, hydrogen peroxide and benzalkonium chloride. Furthermore, Wirtanen et al (2001) demonstrated that commercial disinfectants based on amphoteric surfactants were the least effective in removing biofilms formed by several foodborne pathogenic micro-organisms (Pseudomonas fragi, Enterobacter sp., L. monocytogenes and Bacillus subtilis) on stainless steel for 2 days at 30°C, when compared to sodium hypochlorite-and sodium hydroxide-based disinfectants, among others.…”
Section: Resultsmentioning
confidence: 99%